Dynamic Autoinhibition of the HMGB1 Protein via Electrostatic Fuzzy Interactions of Intrinsically Disordered Regions. Issue 18 (3rd September 2021) - Wang, Xi; Greenblatt, Harry M.; Bigman, Lavi S.; Yu, Binhan; Pletka, Channing C.; Levy, Yaakov; Iwahara, Junji
Graphical abstract: Highlights: The intrinsically disordered regions (IDRs) of HMGB1 undergo fuzzy interactions. Weak fuzzy interactions of the D/E repeats create strong autoinhibition of HMGB1. The IDRs are mobile both in the autoinhibited and uninhibited states of HMGB1. The release of the autoinhibition involves alteration in the fuzzy interactions. Post-translational modifications near the D/E repeats modulate DNA-binding affinity. Abstract: Highly negatively charged segments containing only aspartate or glutamate residues ("D/E repeats") are found in many eukaryotic proteins. For example, the C-terminal 30 residues of the HMGB1 protein are entirely D/E repeats. Using nuclear magnetic resonance (NMR), fluorescence, and computational approaches, we investigated how the D/E repeats causes the autoinhibition of HMGB1 against its specific binding to cisplatin-modified DNA. By varying ionic strength in a wide range (40–900 mM), we were able to shift the conformational equilibrium between the autoinhibited and uninhibited states toward either of them to the full extent. This allowed us to determine the macroscopic and microscopic equilibrium constants for the HMGB1 autoinhibition at various ionic strengths. At a macroscopic level, a model involving the autoinhibited and uninhibited states can explain the salt concentration-dependent binding affinity data. Our data at a microscopic level show that the D/E repeats and other parts of HMGB1 undergo electrostatic fuzzy interactions, each of which is weaker than expected from the macroscopic autoinhibitory effect. This discrepancy suggests that the multivalent nature of the fuzzy interactions enables strong autoinhibition at a macroscopic level despite the relatively weak intramolecular interaction at each site. Both experimental and computational data suggest that the D/E repeats interact preferentially with other intrinsically disordered regions (IDRs) of HMGB1. We also found that mutations mimicking post-translational modifications relevant to nuclear export of HMGB1 can moderately modulate DNA-binding affinity, possibly by impacting the autoinhibition. This study illuminates a functional role of the fuzzy interactions of D/E repeats.